2018
DOI: 10.1002/cmdc.201700660
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prodrug of a γ‐Glutamylcyclotransferase Inhibitor Suppresses Cancer Cell Proliferation in vitro and Inhibits Tumor Growth in a Xenograft Mouse Model of Prostate Cancer

Abstract: γ-Glutamylcyclotransferase (GGCT) depletion inhibits cancer cell proliferation. However, whether the enzymatic activity of GGCT is critical for the regulation of cancer cell growth remains unclear. In this study, a novel diester-type cell-permeable prodrug, pro-GA, was developed based on the structure of N-glutaryl-l-alanine (GA), by structure optimization using temporary fluorophore-tagged prodrug candidates. The antiproliferative activity of pro-GA was demonstrated using GGCT-overexpressing NIH-3T3 cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Recently, it has been reported that the downregulation of GGCT elicits an anti-proliferative effect in some cancer cell lines, such as breast cancer cell lines MCF-7, MCF-7/ADR, and MDA-MB-231 [44][45][46]. Interestingly, ChaC1 was suggested as a novel biomarker because the overexpression of mammalian ChaC1 and its related transcript variants has been previously found to promote cell proliferation in breast cancer cell lines Hs578T and BT-20 [18,47,48].…”
Section: Chac2 Overexpression Promotes Cell Proliferation In the Mcf-mentioning
confidence: 99%
“…Recently, it has been reported that the downregulation of GGCT elicits an anti-proliferative effect in some cancer cell lines, such as breast cancer cell lines MCF-7, MCF-7/ADR, and MDA-MB-231 [44][45][46]. Interestingly, ChaC1 was suggested as a novel biomarker because the overexpression of mammalian ChaC1 and its related transcript variants has been previously found to promote cell proliferation in breast cancer cell lines Hs578T and BT-20 [18,47,48].…”
Section: Chac2 Overexpression Promotes Cell Proliferation In the Mcf-mentioning
confidence: 99%
“…Recently, the first cell membrane permeable GGCT inhibitor has been developed by Ii et al [ 32 ]. As the structure of an inhibitor of enzymatic activity often resembles the structure of the natural substrate of the enzyme, 18 compounds structurally similar to γ-glutamyl- l -amino acid were selected as candidates for GGCT inhibition.…”
Section: Development Of Ggct Inhibitorsmentioning
confidence: 99%
“…In the present study, GGCT was revealed to be increased in CRC tissues compared with normal colon tissues, and patients with CRC that had higher GGCT expression exhibited a worse prognosis compared with patients with a lower expression of GGCT, indicating the prognostic value of GGCT. The dysregulation of GGCT has been reported in certain cancer types, for example Li et al ( 13 ) demonstrated that GGCT suppressed the progression of prostate cancer, indicating that GGCT may serve as a tumor suppressor gene. However, Zhang et al ( 30 ) indicated that the disruption of GGCT inhibited proliferation and induced late apoptosis in human gastric cancer, demonstrating that GGCT may serve as an oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…GGCT has been reported to accumulate in a variety of cancer types, including breast, ovarian, cervical, lung, bladder, prostate, colon, osteosarcoma and glioma, indicating that it may serve as an oncogene in these tumor types ( 7 12 ). The depletion of GGCT has been indicated to inhibit the proliferation of bladder cancer cells and induce the cytotoxicity of McF-7/ADR cells in vitro and in vivo ( 13 ). In previous years, one study has identified the suppression of cancer cell proliferation by disrupting GGCT, highlighting the potential for treatment of malignant tumor types through inhibiting GGCT ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation